Protection From Domestic Violence: An Essential Human Right or a “Fight” Against Masculinity? - ZAKSAITĖ, SALOMĖJA (Kriminologijos studijos, 2017)
I object to violence because when it appears to do good, the good is only temporary; the evil it does is permanent.M. GandhiDomestic violence is associated with various contemporary legal and cultural issues: fundamental human rights, non-discrimination, hatred, feminist theories, Western roots of aggression etc. In this article, the protection from domestic violence is viewed in the light of national and international laws, of the jurisprudence of the European Court of Human Rights, as well as of certain criminological insights. The structure of the research is divided as follows: first, the substantive issues of domestic violence and the concept of such aggressive actions are investigated. To illustrate the relation between international, criminal, civil and social security law, a schematic interaction between the aforementioned substantive laws is introduced. Secondly, procedural issues are analyzed, certain good practice examples are presented and reflections on law-making are laid out.
Keywords: Domestic Violence; Legal intervention; Predicting domestic violence